The Arab-Byzantine Struggle in the 10th Century in the Light of "Synopsis chronike" by Constantine Manasses - Brzozowska, Zofia A.; Leszka, Mirosław J.; Marinow, Kirił; Wolińska, Teresa; Agnieszka Gralak (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
Artykuł jest poświęcony obrazowi zmagań arabsko-bizantyńskich – za panowania Romana II, Nicefora II Fokasa I Jana Tzymiskesa – w Przeglądzie historii Konstantyna Manassesa (XII w.).